Internal Auditor’s Responsibilities for Quality Control of Financial Reporting at PT Asabri (Persero): A Qualitative Analysis - Haryani, Feni; Nasta’in, Fitria; Novitasari, Ika; Putri, Wahyu; Manurung, Herlina (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This article focuses on the quality of financial reporting that needs to be considered because it is an important factor in decision making of a company or agency, including PT Asabri (Persero). Internal auditors control an important role in terms of improving accounting standards, so it will also be discussed about the function and role of internal auditors in minimizing data manipulation in financial reporting. This research uses the literature review method which refers to the process of identifying and evaluating several previous research articles to obtain deeper information about the responsibilities of internal auditors including responsibilities for quality control of financial reporting. The results show that internal auditors have an important role in controlling the quality of financial reporting from manipulation at PT Asabri (Persero).